If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5 + -4z)(5 + 4z) = 0 Multiply (5 + -4z) * (5 + 4z) (5(5 + 4z) + -4z * (5 + 4z)) = 0 ((5 * 5 + 4z * 5) + -4z * (5 + 4z)) = 0 ((25 + 20z) + -4z * (5 + 4z)) = 0 (25 + 20z + (5 * -4z + 4z * -4z)) = 0 (25 + 20z + (-20z + -16z2)) = 0 Combine like terms: 20z + -20z = 0 (25 + 0 + -16z2) = 0 (25 + -16z2) = 0 Solving 25 + -16z2 = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-25' to each side of the equation. 25 + -25 + -16z2 = 0 + -25 Combine like terms: 25 + -25 = 0 0 + -16z2 = 0 + -25 -16z2 = 0 + -25 Combine like terms: 0 + -25 = -25 -16z2 = -25 Divide each side by '-16'. z2 = 1.5625 Simplifying z2 = 1.5625 Take the square root of each side: z = {-1.25, 1.25}
| -(x-9)=3x+17 | | 8x+5(4x-3)=4(6x+4)-4 | | 3(c+7)=36 | | 7(2e-1)-3=6+3e | | x^2+26x-3552=0 | | 3+6x+7+4x= | | 9*x-9=3(3*x-3) | | 4(2x+5)=6(3x-5) | | 25-2x=x | | 3.5d+5.75=2+4.25d | | (5x-8)(2x-6)= | | -19-1+26-37=-1-3m-8+4m | | 8500=-200t^2+3600t | | 3*x+(-4)=6*x-4 | | 90=-2.5b | | 1.3+1.5=1.4 | | 4(2*x+2)=8*x+9 | | 6m-12n= | | .5x+8=1-.25x-7 | | Y=100x^2-81 | | 2a+-2=15.7 | | 55=0.2(55-10e) | | (10x-4)=12 | | 5z-14=8z+4 | | -n+7=n-9 | | x+x(2)+x+86=180 | | -2(6x-4)=8-12*x | | -6d=-8 | | 6-3x+2x^2-x^3=0 | | -x=7x+2 | | 4*x+19=-9-6x | | x+5=7x+2 |